The dynamics of child poverty in Ireland: Evidence from the growing up in Ireland survey - Bertrand Maître; Helen Russell; Emer Smyth (The Economic and Social Research Institute (ESRI), 2021)
New ESRI research finds that relationship breakdown and mothers' or fathers' job loss are key triggers for transitions into child poverty. Living in poverty, especially over a protracted period of time, has far-reaching consequences for children's development and wellbeing. The study is part of a research programme between the ESRI and the Department of Children, Equality, Disability, Integration and Youth, and is being launched today by Minister O'Gorman.
Keywords: 330